(3GdaGYdhf GdeSdMhf ef ZjQ GdOhd hGSJNOGe WGFQGJ GdOQhfR aj GdYGde GdYQHj (B:s (3GdhVY GdQGgf hBaGb GdeSJbHd (B/s - (3EHQGgje, MSfjf Jhajbs ([(3GdEeGQGJ GdYQHjI GdeJMOI(B] :s (3JQjfOR ddHMhK hGdGSJTGQGJ,s, 2021)
(3JeKd XGgQI GdaGYdjf GdeSdMjf ef ZjQ GdOhd hGMOI ef CHQR GdJMOjGJ GdJj JhGLg GdYGde GdYQHj aj GdhbJ GdQGgf, hbO CUHM HYV gDdGA GdaGYdjf CcKQ NWhQI eY GJLGgge fMh GSJNOGe WGFQGJ GdOQhfR aj GdeLGd GdYScQj, hef CHQR GdaGYdjf GdeYfjjf (B"(3GdMhKjhf(B" (3h(B"(3MRH Gddg(B" (3h(B"(3MQcI GdebGheI GdESdGejI(B" ((3MeGS(B)(3, hHYV aUGFd GdMTO GdTYHj GdehGdjI dEjQGf, ceG JMhdJ cd ef djHjG hShQjG aj Xd GdMQH GdCgdjI GdJj TgOJgG cd ef GdOhdJjf Edi SGMI dGSJNOGe CfhGY eNJdaI ef WGFQGJ GdOQhfR, ShGA ef bHd Ohd Ch aGYdjf eSdMjf ef ZjQ GdOhd(B. (3hJQcR gPg GdOQGSI Ydi QUO hJMdjd eXGgQ hCSHGH JUGYO gPg GdXGgQI, aVdG Yf JMdjd hJbjje JOGYjGJgG Ydi bVGjG GdCef hGdGSJbQGQ, hYedjI HfGA GdOhdI GdhWfjI aj GdefWbI, hJYfi cPdc HGSJTQGa BaGbgG GdeSJbHdjI(B. (3hjfJTQ GdaGYdhf GdeSdMhf ef ZjQ GdOhd GdCcKQ GSJNOGeG dWGFQGJ GdOQhfR aj Ohd YQHjI VYjaI heJUOYI, ceG JYJHQ EjQGf ef Gdbhi GdQFjSjI GdJj CSgeJ(B-(3hdGJRGd(B-(3aj GSJeQGQjI XGgQI GdaGYdjf GdeSdMjf ef ZjQ GdOhd aj GdYGde GdYQHj, haj JYRjR GdbOQGJ GdYScQjI dHYV gDdGA GdaGYdjf ef NdGd JRhjOge HWGFQGJ OQhfR hZjQgG ef GdCSdMI, hJhXa EjQGf hcdGAgG aj GdefWbI ef CLd JMbjb CgOGagG, MjK JYJHQge echfG egeG Vef GSJQGJjLjJgG GdCefjI hGdOaGYjI(B. (3heGOGeJ XGgQI GdOhd GdVYjaI hGdeJUOYI aj GdYGde GdYQHj eSJeQI aSha JSJeQ eYgG XGgQI GdaGYdjf GdeSdMjf ef ZjQ GdOhd, hfXQG ddeRGjG GdYOjOI GdJj JhaQgG dge WGFQGJ GdOQhfR aSha jSYj gDdGA GdaGYdhf dJYRjR bOQGJge GdYScQjI GYJeGOG Ydi gPG GdSdGM GdQNjU hGdeDKQ, hef GdeJhbY Cf jJhSY HYV gDdGA GdaGYdjf aj JUfjY HYV CfhGY WGFQGJ GdOQhfR hJWhjQ fXe JSdjMgG, GdCeQ GdPj jYeb ef eUGOQ GdNWQ hGdJgOjO Ydi GdOhd hGdeLJeYGJ(B.s
(3HHdjhLQGajI (B: (3UaMI (B47-56.s
Keywords: (3GdEQgGHs -- (3LhGfH SjGSjIs -- (3GdHdGO GdYQHjIs; (3GdLgGJ GdaGYdI ZjQ GdMchejI (B((3YdGbGJ NGQLjI(B)s -- (3GdHdGO GdYQHjIs; (3GdYfa GdSjGSjs -- (3GdHdGO GdYQHjIs